Waste Generation and Composition in Karawang Regency - Salman, Nurcholis; Iskandar, Anan; Noviyanti, Estin; Mellyanawaty, Melly (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
Sources of waste in Karawang Regency come from various activities of residents who are concentrated in locations such as residential, commercial, social facilities and public facilities. Each source of waste has characteristics for the generation, composition and characteristics of the resulting waste. In general, the source of waste is divided into household (domestic) and non-household (non-domestic). It is known that the generation of waste for the domestic sector of households is 2.93 L/person/day or 0.42 Kg/person/ day. But when viewed from the economic level, high income housing has the highest generation of 3.27 L/person/day. This is because differences in economic level and lifestyle affect the consumption level of the residents of the House. The higher the level of community life, the greater the waste generation. Based on the calculation results, it is known that the value of waste generation of each facility is different. This is because each facility has different activities. Shops have the highest generation of 3.78 L/person/day, followed by markets and roads as much as 1.55 L/m2/day and 1.12 L/ m2/day. This indicates that the activity of the store produces more waste than the market and the street. When reviewing the waste generation of Karawang Regency, the generation is greater than the domestic sector alone. The result of one area of Karawang Regency showed the waste generation is 0.56 Kg/person/day or 4.06 L/person/day.